Patriarchy and Apocalypse in Cerca del fuego by José Agustín - Cynthia Steele (Studies in 20th & 21st Century Literature, 1990)
José Agustín's novel is one of several Mexican texts that depict the nation in ruins, but although the novel is parricidal in its parody of its literary antecedents, it is underpinned by a Jungian quest for wholeness. The protagonist's spiritual adventures take him through the subterranean experience of limits (and through the lower depths of Mexico City), only to end with the reconstitution of the "fatherland" and the family.
Keywords: Mexican literature; José Agustín; nation in ruins; Jungian; Jung; spirituality; limits; limitation; fatherland; family